MENAKAR IMPLIKASI GOVERNMENT SPENDING SEKTOR HULU MIGAS - Puji Wibowo (SUBSTANSI, 2017)
Upstream oil and gas in Indonesia has been very popular since the first implementation of Production Sharing Contract (PSC) in 1970s. One of the attractivenesses of Indonesian PSC is contractors shall not be burden by indirect taxes and other charges if they succeed to economically produce oil or gas and surrender to government. The mechanism of indirect taxes and other charges payment by Indonesian Government is not an ordinary system. The cash disbursement for fulfilling government’s liabilities in upstream oil and gas sector is taken out from Oil and Gas Account, which is beyond form General State Account. This study attempts to analyze a number of problems arise in this off-budget scheme. This paper is also trying to evaluate established government expenditure regime in order to formulate recommendation. Based on our research, we conclude that policy concerning budget planning, execution, and reporting should be reconsidered, by taking fiscal impact into account, to improve the level of accountability and transparency.